Depression, anxiety, and stress related to online distance learning (ODL) does not influence academic performance : findings from an online survey among undergraduates in Malaysia - Sumaiyah Mat,; Vivian Sheereen anak Rantai,; Lo, Isaac Sheng Jieh; Adibah Nabilah Zulkiply,; Alif Najmi Amaluddin,; Nabil Amin Mohamed Yusof,; Ho, Wei Sheng; Ahmad Nabil Khairi Mahdzir,; Nor Azlin Mohd Nordin,; Normala Mesbah,; Deepashini Harithasan,; Nor Azura Azmi,; et al. (Penerbit Universiti Kebangsaan Malaysia, 2021)
While there has been widespread reporting of a negative impact on students' mental health and academic performance because of ineffective online learning systems during COVID, Malaysian data remained scarce. In this online survey, the correlation between online distance learning (ODL), mental health status and academic performance of Malaysian undergraduates during COVID-19 pandemic were examined. Academic performance was measured using self-reported questionnaires in which respondents were also asked to state their cumulative grade points average (CGPA). Reduction in CGPA was considered as a decline in academic performance. Data on ODL readiness and satisfaction as well as mental health status were obtained. Among 256 respondents of this study with mean age (SD) 22.10 (1.05), a total of 27.3% reported to have decline in CGPA during Covid-19 pandemic. Female undergraduates were more likely to perform better as more had maintained or improved their academic performance. Self-directed learning, learning control, learning motivation, and satisfactionwere significantly associated with academic performance (p<0.05) but not computer-internet self-efficacy and online communication self-efficacy. There were also significant negative correlations between ODL and Mental Health Status. However, mental health status does not appear to be significantly associated with decline in academic performance. Our study findings suggest that ODL preference and satisfaction have an impact on the academic performance. While, mental health status related to ODL was not associated with academic performance. Students getting used to the shift into remote learning over time may explain why mental health status had no effect on their academic performance. Future studies should focus on the know how to deliver effective ODL techniques to improve undergraduates’ satisfaction with the hope to further improve their academic performance.